Asbestos : medical and legal aspects - Castleman, Barry L. (New York, 2005)
"Written by one of the leading asbestos experts for both plaintiff and defense attorneys, occupational and environmental health professionals, as well as others in the field of toxic substances control, Asbestos: Medical and Legal Aspects has become the definitive resource on the medical and legal aspects of asbestos. Asbestos: Medical and Legal Aspects provides a comprehensive examination of the public health history of asbestos, from the origins of industrial use to the present. It includes in-depth coverage of prior and ongoing litigation; extensive evaluation of the legal arguments put forth by plaintiff and defense counsel; and provides crucial information, materials and resources on the evolving corporate knowledge of asbestos hazards. The book covers in detail: asbestosis and cancer; compensability of asbestosis and cancer as occupational diseases; thresholds and standards used to determine safe or acceptable levels of asbestos exposure in the workplace; and company knowledge of asbestos hazards, gleaned from countless depositions, company records, industry consultants and trade associations. Some items new to the Fifth Edition include: - extensive discussion of corporate knowledge and responsibility for asbestos hazards - extensive examination of the international struggle over asbestos, whereby some countries have banned asbestos while others have continued to expand their usage of asbestos in building materials - detailed discussion of alternatives to asbestos."